Moral Internalisation In The Character Development Of Young Martial Art at The Tapak Suci Sumedang Training Centre - Muhammad Rizal Iskandar; Tedi Supriyadi; Muhammad Nur Alif (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study aims to analyse the process of moral internalisation in shaping the character of adolescent martial arts students at the Tapak Suci Training Centre in Sumedang. The study highlights the novelty of martial arts education as a holistic medium for integrating moral, spiritual, and behavioural development among adolescents. A qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings show that moral internalisation occurs through the integration of cognitive (moral knowing), affective (moral feeling), and behavioural (moral action) dimensions. These dimensions interact continuously within adolescents’ social environments and daily training activities. Family support and a positive social environment strengthen the implementation of moral values outside the training centre. In contrast, negative peer influence, conflicting environmental values, unstable adolescent psychology, and inconsistency in practising moral values become inhibiting factors. The study also reveals that adolescents interpret the organisation’s motto not only as physical strength but also as spiritual and moral strength. This internalisation is reflected in disciplined behaviour, responsibility, and self-control in everyday life. Therefore, effective moral internalisation requires consistent support from family, community, and educational environments to sustain adolescent character development.